Supporting Entrepreneurs at the Local Level : The Effect of Accelerators and Mentors on Early-Stage Firms - Qian, Kathy; Mulas, Victor; Lerner, Matt (World Bank, Washington, DC, 2018)
We investigate the association between entrepreneurship support programs and the likelihood of receiving funding for early-stage firms. We use a novel database of 2,887 early-stage technology companies from nine local ecosystems in eight countries that includes data about the founders’ demographic characteristics, educational background, work experience, and entrepreneurial history; we also use data about the start-ups’ history and evolution that follow their progress through support programs and early-stage funding. We isolate two support interventions—acceleration and mentorship—that the literature has found to have a larger effect on a firm’s performance, and we test if such effect is supported from an ecosystem perspective. After accounting for variations in founder characteristics and business environment, we find a positive association between acceleration and mentorship by experienced founders and the likelihood of receiving funding, whereas other support programs, such as incubation, are negatively correlated with funding. We also find that some founders’ characteristics, such as increased education and experience, have a positive correlation with funding.